Evaluation of functional status among patients undergoing maintenance treatments for opioid use disorders - Juan J. Ruíz Ruíz; José M. Martinez Delgado; Nuria García-Marchena; The ANDOPIO Study Group (BMC, 2021)
Abstract Background Methadone and buprenorphine are the most prevalent types of opioid maintenance programs in Andalusia. The main objective is comparing the functional status of patients with pharmacological opioid maintenance treatments according to different socio-demographic characteristic, health and disabilities domains and sexual difficulties. Methods A total of 593 patients from the Andalusia community, 329 were undergoing methadone treatment and 264 were undergoing buprenorphine treatment. The patients were interviewed by socio-demographic and opioid-related variables, assessed by functioning, disability and health domains (WHODAS 2.0.) and for sexual problems (PRSexDQ-SALSEX). Results We found significant differences in the socio-demographic and the opioid-related variables as the onset of opioid use, being on previous maintenance programs, opioid intravenous use, the length of previous maintenance programs, polydrug use and elevated seroprevalence rates (HCV and HIV) between the methadone group and the buprenorphine group. Regarding health and disability domains there were differences in the Understanding and communication domain, Getting around domain, Participation in society domain and in the WHODAS 2.0. simple and complex score, favoring buprenorphine-treated patients. The methadone group referred elevated sexual impairments compared with the buprenorphine group. Opioid-related variables as seroprevalence rates, other previous lifetime maintenance program, the daily opioid dosage and the daily alcohol use are the most discriminative variables between both groups. Participation in society variables and sexual problems were the most important clinical variables in distinguishing the methadone group from the buprenorphine group regarding their functional status. Conclusions The methadone group showed higher prevalence in opioid dependence-related variables, elevated disabilities in participation in society activities and sexual problems compared with the buprenorphine group. This study shows the importance of carry out a functional evaluation in the healthcare follow-up, especially in those areas related with social activity and with sexual problems.